STRATEGI PROMOSI WISATA PURBALINGGA MELALUI FESTIVAL FILM - Dewi Sad Tanti; Ginanjar Ginanjar (Jurnal Visi Komunikasi, 2020)
This study aims to find out the efforts to promotion strategy Purbalingga cultural tourism by the Purbalingga CLC community through the Purbalingga Film Festival (FFP). This study used descriptive qualitative method. The research data source is the Purbalingga CLC community. Data was collected using observation techniques, in-depth interviews, and literature studies. The results showed that FFP activities carried out by the CLC community could help Purbalingga tourism promotion efforts. Local tourism development can be developed with the concept of Community Based Tourism (CBT) is Promotion strategy. In the CBT concept, the presence of the community becomes important as a secondary stakeholder. Together with the government and private parties, community participation can provide valuable input for the advancement of regional tourism that is prospering for the entire community. The Purbalingga CLC through its flagship program, the Purbalingga Film Festival, has shown that the existence of film festivals has a relationship, both directly and indirectly, with the opportunity to promote local culture.